Global Compendium of Land Value Capture Policies (OECD Regional Development Studies, 2022)
The Global Compendium of Land Value Capture, a joint project by the OECD and the Lincoln Institute of Land Policy, is an ambitious undertaking to understand the full landscape of land value capture (LVC) instruments, how they are configured and deployed across the globe in OECD countries and non-OECD economies, and what it would take to unleash their full potential as a sustainable revenue source. Moreover, little systematic information is available about the LVC instruments that countries use and enabling frameworks at national and regional levels to guide local governments toward greater use. The report features an overview of the political contexts, legal frameworks, and LVC approaches used in 60 countries. Special attention is given to the differences and similarities between countries that have a mature LVC practice, versus countries that have nascent policies and allowances. This will help countries developing the capacity and competences for LVC to understand the opportunities, trade-offs, and pitfalls to avoid when configuring legal, governance, and planning frameworks and institutions to support the implementation of LVC policies.